E-014 Endovascular endothelial biopsy of intracranial aneurysms for personalized risk stratification using single cell RNAseq. (4th August 2020) - Young, C; Levy, S; Patel, A; Cooke, D; Zheng, Y; Mandrycky, C; Kelly, C; Kim, L; Levitt, M
Abstract : Introduction: Early detection and treatment of intracranial aneurysms can prevent hemorrhagic stroke. However, treatment requires an invasive surgical procedure, which is potentially risky and costly. Risk quantification systems based on aneurysm size are imperfect since the majority of ruptured aneurysms are small, and no robust method exists for predicting an individual aneurysm's likelihood of rupture. Endothelial cell (EC) genetics have been proposed to play a critical role in aneurysm risk. However, with the advent of endovascular treatment of aneurysms, there is a decline in the availability of biological tissue for research. Method: We used a minimally-invasive endovascular EC collection technique to obtain aneurysmal ECs from aneurysm coils and access sheaths during endovascular treatment. Cells were collected from unruptured and ruptured aneurysms with low- and high-risk PHASES scores, as well as control arteries. After fluorescent-activated cell sorting (FACS), cytoplasmic mRNA from individual cells were extracted with SmartSeq Single Cell TM and cDNA libraries were constructed for single cell RNA-Seq. Results: Non-deployed endovascular coils and access sheaths from 15 patients (8 unruptured and 7 ruptured aneurysms) with a median PHASES score of 7, ranging from 3 – 11, were safely collected during endovascular treatment without adverse event. Cells were dissociated from the hardware and viable endothelial cells were identified by FACS with CD31 antibodies in 8 patients (5 unruptured and 3 ruptured aneurysms. Extracted RNA from single cells produced >500 pg of cDNA which was used for cDNA library construction and submitted for RNA sequencing. Conclusion: Endovascular sampling of unruptured and ruptured aneurysm is safe and feasible. Despite the dissociation and FACS processes, endothelial cells were viable and produced sufficient cDNA at a single cell level for the construction of cDNA library for RNA sequencing. We envisage that this technique will greatly enhance the availability of cellular material for genetic study of cerebrovascular diseases. Disclosures: C. Young: 1; C; AANS/CNS CV Section Robert J Dempsey Award 2019/2020, Bee Foundation Aneurysm Research Grant. S. Levy: None. A. Patel: None. D. Cooke: None. Y. Zheng: None. C. Mandrycky: None. C. Kelly: None. L. Kim: None. M. Levitt: None.